PENGARUH STRATEGI PRODUK, STRATEGI HARGA TERHADAP EKUITAS MERK DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN DAN LOYALITAS (Studi empiris pasca pembelian AC/Air Conditioner merk Polytron di Kudus) (Students' Journal of Economic and Management, 2013)
This study aimed to determine the effect of pricing strategy and product strategy for the brand equity and its impact on purchasing decisions and loyalty. The population in this study is their (consumer) users in the holy AC Polytron with minimal use of one year. Sampling was done by using "purposive sampling" so that the samples taken can represent the study population. Engineering test data used in this study include the test instrument consisting of validity and reliability, the test model consists of regression and coefficient of determination, and hypothesis testing. From the analysis of the path lines can be seen that the direct effect of price and product purchase decisions indirect effect of price and product purchase decisions, so the track is better research is not through brand equity. Variable pricing, products and brand equity together - together have accounted for 61.8% of the purchasing decisions AC Polytron users. While the remaining 38.2% is influenced by other variables not included in this study Keywords: pricing strategy, product strategy, brand equity, loyalty and purchasing decisions.